Triptolide, an Inhibitor of the Human Heat Shock Response That Enhances Stress-induced Cell Death - Westerheide, Sandy D.; Kawahara, Tiara L.A.; Orton, Kai; Morimoto, Richard I. (The Journal of biological chemistry, 2006)
Molecular chaperones, inducible by heat shock and a variety of other stresses, have critical roles in protein homeostasis, balancing cell stress with adaptation, survival, and cell death mechanisms. In transformed cells and tumors, chaperones are frequently overexpressed, with constitutive activation of the heat shock transcription factor HSF1 implicated in tumor formation. Here, we describe the activity of triptolide, a diterpene triepoxide from the plant Triptergium wilfordii, as an inhibitor of the human heat shock response. Triptolide treatment of human tissue culture cells prevented the inducible expression of heat shock genes, shown by suppression of an HSP70 promoter-reporter construct and by suppression of endogenous HSP70 gene expression. Upon examining the steps in the HSF1 activation pathway, we found that triptolide abrogates the transactivation function of HSF1 without interfering in the early events of trimer formation, hyperphosphorylation, and DNA binding. The ability of triptolide to inhibit the heat shock response renders these cells sensitive to stress-induced cell death, which may be of great relevance to cancer treatments.